Acoustic characterization of automotive turbocompressors. (January 2015) - Torregrosa, Antonio J; Broatch, Alberto; Navarro, Roberto; García-Tíscar, Jorge
The performance of different experimental techniques proposed in the literature for acoustic characterization was assessed through the study of the noise generated by the compressor of an automotive turbocharger under different working conditions in an engine test cell. The most critical restrictions of in-duct intensimetry methods regarding frequency limitations are presented and experimentally demonstrated. The results provided by those methods were correlated against a reference intensity probe. A beamforming method based on three-sensor-phased arrays appears to be the most reliable approach in the plane wave range, presenting higher accuracy than the more common two-microphone method and simple pressure level measurements. Also, preliminary results from a novel radiated noise quantification technique based on acoustic particle velocity are presented and discussed. The results indicate that further research on this topic is required.